The Effect of Professional Certificate Teachers Performance on Student Learning Achievements in The Eyes Vocational Private School - Sintia S; Nanang Dalil Herman; Istiqomah Istiqomah (Universitas Pendidikan Indonesia, 2021)
The teacher certification program is one of the governmentprograms that aims to improve teacher performance incarrying out their teaching assignments. Improved teacherperformance, is expected to improve student achievementoutcomes. This study aims to determine the general pictureof professional certified teachers performance, the result ofstudent achievement, and to find out the influence ofprofessional certified teachers performance on the results ofstudent achivement in the vocational learning in SMK Negeri1 Sumedang. The research method used is the EkspalantoryResearch method with a quantitative approach. The numberof research samples as many as seven (7) teachersspecializing in vocational learning in building design andinformation design competencies (DPIB) who have passedprofessional certification. Several studies stated that thecertification program had not had a significant impact onteacher performance. In terms of certification, the programhad to be viewed from various aspects in detail, not onlyfrom the learning aspect.